2004
DOI: 10.1111/j.1475-1313.2004.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Correctable visual impairment in older people: a major unmet need

Abstract: This review seeks to determine the prevalence of correctable visual impairment (VI) in older people in the UK, to discover what proportion of these cases are undetected, to suggest reasons for the poor detection and to make recommendations for improving the detection. To establish the context of these issues, the review will also touch on the general prevalence and causes of VI in older people in developed countries and on the impact of VI in older people. Typically, studies suggest that VI affects about 10% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 91 publications
(185 reference statements)
3
108
0
3
Order By: Relevance
“…9,10 Studies investigating sight loss and dementia have revealed shared changes in nervous system physiology and suggest that the prevalence of sight loss in people with dementia is higher than that in the general population of older people without dementia. 10 People with dementia not only suffer the general visual problems associated with ageing but also experience deficits of higher level visual processing including reading, object recognition and spatial localisation as a result of the damage to, or degeneration of, the brain, 11 which can make the differential diagnosis of 'eye problems' from functional vision loss caused by dementia or, for example, stroke more difficult. The effects of having both serious sight loss and dementia concurrently are much more severe than those resulting from either dementia or sight loss alone.…”
Section: Dementia and Sight Lossmentioning
confidence: 99%
“…9,10 Studies investigating sight loss and dementia have revealed shared changes in nervous system physiology and suggest that the prevalence of sight loss in people with dementia is higher than that in the general population of older people without dementia. 10 People with dementia not only suffer the general visual problems associated with ageing but also experience deficits of higher level visual processing including reading, object recognition and spatial localisation as a result of the damage to, or degeneration of, the brain, 11 which can make the differential diagnosis of 'eye problems' from functional vision loss caused by dementia or, for example, stroke more difficult. The effects of having both serious sight loss and dementia concurrently are much more severe than those resulting from either dementia or sight loss alone.…”
Section: Dementia and Sight Lossmentioning
confidence: 99%
“…An analysis of the figure below shows that, next to burns (51 %) and cuts (33 %), some of the more frequent dangerous In direct interviews a large number of respondents pointed to the problem of loss of balance when performing everyday activities. It is estimated that the elderly people and individuals with low vision fall twice as often as people with normal vision (Evans and Rowlands, 2004). The problem of balance disturbances of the elderly was also indicated by Kabsch (2000), who stressed that mortality caused by fall accidents increases drastically after 70 years of age (Kabsch, Based on the analysis of data presented in Figure 3, safer solutions can be designed taking into consideration the needs of people with visual impairment.…”
Section: Rezultat I Raspravamentioning
confidence: 99%
“…It is essential to undertake studies on the identification of needs of this group of users, particularly as it has been proven that there is a strong dependence between visual impairment at an older age and a lower standard of living and greater probability of accidents (Evans and Rowlands, 2004 Thus the aim of this study was to collect information concerning both preferences and problems faced by the elderly or middle-aged individuals with visual impairment when working in the kitchen. An additional practical objective was to propose examples of ready design solutions for kitchen furniture for individuals aged 65+ with visual impairment.…”
Section: Uvodmentioning
confidence: 99%
“…According to a randomized clinical trial in England, early treatment for amblyopia leads to better outcomes than later treatment; and such treatment has been shown to be cost-effective [53,54]. For older adults, uncorrected refractive error is a primary cause of reduced vision [55]; however, refractive error correction has been shown to significantly improve quality of life within this population [56]. Overall, these studies help to support our recommendations, particularly for infants and children, as a means to facilitate early detection and treatment of problems such as strabismus, anisometropia and high refractive errors.…”
Section: Periodic or Routine Comprehensive Optometric Eye Examinationsmentioning
confidence: 99%